PENGARUH PEMBERIAN TERAPI AIR HANGAT TERHADAP PENURUNAN TEKANAN DARAH PADA LANSIA DENGAN HIPERTENSI - Gito -; Reni Dwi Setyaningsih; Refa Teja Muti (Viva Medika, 2016)
Hypertension is one of the global public health problem. Management of overcominghypertension include two types of management, they are pharmacological and nonpharmacologicalmanagement.Oneofnon-pharmacologicalmanagementisawarmwatertherapy. Warm water therapy is useful in reducing muscle contractions that can lead to a relaxed feellingand reduce hypertension. The purpose of this research was to know the difference in bloodpressure before and after the warm water therapy in patients with hypertension at tambaksari,kembaran. this research used pre experiment method with one group pre-test and post-test design.Research instrument used were sphygmomanometer, stethoscope, thermometer and observationsheet. Population and sample in this research were members of elderly posyandu with hypertensionat Tambaksari. The sampling technique used in this research was Simple Random Sampling.Statistical test used was paired t-test with Î± value was 5%. The results showed that before beinggiven a warm water therapy systolic blood pressure average was of 170 mmHg and diastolic was90,36 mmHg. The result after bing given warm water therapy systolic blood pressure average was155,36 mmHg and diastolic one was 84,64 mmHg. The average decline of systolic blood pressurewas 14, 643 mmHg and 5,714 mmHg of diastolic one. It showed there is a significant difference ofsystolic and diastolic blood pressure before and after being given warm water therapy. Theconclusion of this research that there is the differences in blood pressure before and after beinggiven the warm water therapy in patient (Ï=0,000). Keywords: warm water therapy, elderly, hypertension